Invasive hornets on the road: motorway-driven dispersal must be considered in management plans of Vespa velutina - Verdasca, Maria João (2022)
Understanding the mechanisms that potentiate the dispersion of an invasive species is essential to anticipate its arrival into new regions and to develop adequate management actions to minimize damage to biodiversity and society. One of the most successful invaders in Europe, the yellow-legged hornet (Vespa velutina), is dispersing through self-diffusion and jump dispersal. Using information on species occurrence in Portugal from 2013 to 2018, this study aimed to understand the range expansion trajectory of V. velutina and to identify the role of climate, landscape and anthropogenic variables on the two mechanisms of spread. We found that in Portugal the invasion is proceeding faster southwards (45 km/year) along the Atlantic coast than eastwards (20 km/ year) where the climatic suitability gradient is more compressed, with jump dispersal playing an important role in this difference and in the acceleration of the invasion process. Dispersal by diffusion was best explained by the annual range of temperature and precipitation of the wettest month, with distance to shrub land also having an important role. Additionally, jump dispersal appeared to be facilitated by motorways, hinting at the role of human-mediated dispersal. Indeed, the number of nests that resulted from this dispersive mechanism were significantly closer to motorways than expected by chance. To prevent the dispersal of V. velutina into Mediterranean regions, and in addition to a special attention to the advancing front, early monitoring programs should also target a buffer zone on both sides of motorways, and at freight shipping hubs.